Grain Storage Management in India - Sharon, M Esther Magdalene; Abirami, C V Kavitha; Alagusundaram , K (Journal of Postharvest Technology, 2024)
India’s grain production has steadily increased due to advances in  technology, but post-harvest loss is constant at 10%. Losses  during storage, accounts for around 6% of the total losses as  proper storage facilities are not available. In India, food grains are  stored using traditional structures by small farmers. The surplus  grains are stored with government agencies like: Food  Corporation of India (FCI), Central and State warehousing  Corporations. The commonly used storage method is Cover and  Plinth (CAP) storage, which is economical but loss of grains is  inevitable. Very few scientific storage structures like silos are  available with these agencies. The government is taking  initiatives now in building silos for long-term safe storage of  grains since we do not have enough storage capacity as of now.  Drying of harvested grains to safe moisture levels will reduce  losses to a greater extend. However, very less literature is  available on behaviour of grains after harvest for Indian climatic  conditions. Therefore, there is a need for research to develop  management guidelines for safe storage and drying to ensure  quality management of stored grains.
Keywords: Post-harvest loss; Storage; Cereals; Drying; Guidelines